2011
DOI: 10.1007/s00595-010-4266-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transabdominal preperitoneal approach for inguinal hernia repair: A five-year experience at a single center

Abstract: Laparoscopic TAPP hernia repair has proven to be an efficient method for the treatment of groin hernias at our institution. Most patients can be treated as day-cases, namely they are hospitalized for 1 day, and they demonstrate a low recurrence rate (0.70%). Such low morbidity makes TAPP an attractive method for the routine treatment of groin hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Laparoscopic hernia repair is also associated with shorter hospital stay, faster recovery, earlier return to normal activities (3,9). Better cosmetic results (4), possibilities to detect a contralateral inguinal defect and repair it through the same incision at the same time are the advantages of laparoscopic surgery too (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Laparoscopic hernia repair is also associated with shorter hospital stay, faster recovery, earlier return to normal activities (3,9). Better cosmetic results (4), possibilities to detect a contralateral inguinal defect and repair it through the same incision at the same time are the advantages of laparoscopic surgery too (9).…”
Section: Discussionmentioning
confidence: 99%
“…Better cosmetic results (4), possibilities to detect a contralateral inguinal defect and repair it through the same incision at the same time are the advantages of laparoscopic surgery too (9). The disadvantages of laparoscopic surgery include requirement of general anaesthesia, longer operative time and learning curve (5,8,10,11), more expensive equipment (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the advantages of laparoscopic over open repair with regard to reduced postoperative pain and a lower need for analgesia, an earlier return to physical activity, and better cosmetic results [3,5]. Seromas and hematomas are commonly seen complications after laparoscopic hernia repair.…”
Section: Discussionmentioning
confidence: 99%